2020
DOI: 10.25004/ijpsdr.2020.120211
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Stability Indicating RP-HPLC Method for the Determination of Prucalopride succinate in Bulk and Tablet

Abstract: A very simple, precise, economical, accurate, robust, and reproducible reverse phase-high-performance liquid chromatography method along with stability indicating attributes has been developed for estimating of prucalopride succinate (PRU) in both bulk and tablet formulation (PRUVICT 2). The estimation of the solutes was performed on a Grace C18 column of dimension 150 mm × 4.6 mm, 5 μm. PRU was eluted with acetonitrile: 0.02 M potassium dihydrogen phosphate in the ratio of 20:80 v/v in a 10 min isocratic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…The method was successfully applied to determine the studied drug in pharmaceutical tablet dosage form; the recoveries obtained are summarized in Table 4 . The proposed method showed good agreement when compared with the reference method [ 10 ] regarding accuracy as indicated by the student’s t -test and precision as indicated by the F-test [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method was successfully applied to determine the studied drug in pharmaceutical tablet dosage form; the recoveries obtained are summarized in Table 4 . The proposed method showed good agreement when compared with the reference method [ 10 ] regarding accuracy as indicated by the student’s t -test and precision as indicated by the F-test [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we aimed to use the advantage of the lanthanide-sensitized luminescence to develop and validate an analytical method for the determination of prucalopride succinate (PRU). The IUPAC name of PRU is 4-amino-5-chloro-N-[1-(3-methoxypropyl)piperidin-4-yl]-2,3-dihydro-1-benzofuran-7-carboxamide;butanedioic acid [ 10 ] (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature review revealed the determination of PRU using various analytical techniques including chromatographic [4][5][6][7][8][9][10], spectrophotometric [11] methods and only one reported spectrofluorometric procedure that uses luminescence reaction [12] but there is no quantification in the urine sample. Spectrofluorimetric technique is commonly used in drugs analysis either in dosage form or in biological fluids for its high sensitivity and simplicity [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Literature review revealed the determination of PRU using various analytical techniques including chromatographic [3][4][5][6][7][8][9] , spectrophotometric 10 methods and only one reported spectro uorometric procedure that use luminescence reaction 11 but there is no quanti cation in the urine sample. By taking the bene t of native uorescence of PRU; the proposed method is aimed at developing an easy and rapid assay method for the quantitative determination of PRU in human urine without any time-consuming sample preparation steps for routine analysis.…”
Section: Introductionmentioning
confidence: 99%